Impact of SARS-CoV-2 Infection on Humoral and Cellular Immunity in a Cohort of Vaccinated Solid Organ Transplant Recipients - Bernardo Ayala-Borges; Miguel Escobedo; Natalia Egri; Sabina Herrera; Marta Crespo; Sonia Mirabet; Carlos Arias-Cabrales; Anna Vilella; Eduard Palou; María M. Mosquera; Mariona Pascal; Jordi Colmenero; et al. (Vaccines, 2023)
The aim of the present study was to determine humoral and T-cell responses after four doses of mRNA-1273 vaccine in solid organ transplant (SOT) recipients, and to study predictors of immunogenicity, including the role of previous SARS-CoV-2 infection in immunity. Secondarily, safety was also assessed. Liver, heart, and kidney transplant recipients eligible for SARS-CoV-2 vaccination from three different institutions in Barcelona, Spain were included. IgM/IgG antibodies and T cell ELISpot against the S protein four weeks after receiving four consecutive booster doses of the vaccine were analyzed. One hundred and forty-three SOT recipients were included (41% liver, 38% heart, and 21% kidney). The median time from transplantation to vaccination was 6.6 years (SD 7.4). In total, 93% of the patients developed SARS-CoV-2 IgM/IgG antibodies and 94% S-ELISpot positivity. In total, 97% of recipients developed either humoral or cellular response (100% of liver recipients, 95% of heart recipients, and 88% of kidney recipients). Hypogammaglobulinemia was associated with the absence of SARS-CoV-2 IgG/IgM antibodies and S-ELISpot reactivity after vaccination, whereas past symptomatic SARS-CoV-2 infection was associated with SARS-CoV-2 IgG/IgM antibodies and S-ELISpot reactivity. Local and systemic side effects were generally mild or moderate, and no recipients experienced the development of de novo DSA or graft dysfunction following vaccination.